Perception of language awareness through framegram: a classroom example / Nik Ahmad Farhan Azim@Nik Azim ... [et al.] - Azim@Nik Azim, Nik Ahmad Farhan; Ramamurthy, Lena; Shafien, Syakirah; Mohd Nawi, Noor Syamimie; Mat So’od, Shahidatul Maslina (2021)
Writing in English within the context of English as Second Language (ESL) can be a daunting prospect for many students. Such perennial challenge could potentially be damaging. It is even worse when constructing a piece of writing that requires critical thinking. This research is aimed at answering both conundrums. The research draws the context of Language Awareness (LA) within the framework of Framegram. This framework is used in one of the formative assessments in the university core subject of Adavnced Grammar of Undergraduates (UBI10302): Grammar Article Entry (Instagram Entry). Theoretically, LA is seen as a bridge to connect functional and purposeful language to a given phenomena (issues or problems); characterised by student’s deep interest and critical thinking. While students interact as active participatory editors and publishers of their content on Instagram, such dynamic interaction emerged from relationship between student’s language phenomena may result in predictable output of language learning. Hypothetically, as their ability to manipulate or discriminate the language increasingly progresses parallel to their interest and motivation on a given issue or phenomena, it is likely that their skills and language too will be improved. Consequently, this improves the student’s current writing state in relation to language development and their ability to integrate critical thinking within the process. The research will investigate the extent of usefulness of the Framegram Framework in this course. Ultimately, the data gathered will serve as an informed decision of how the language learners perceived LA as part of their second language learning experience.